2005
DOI: 10.1108/07363760510595977
|View full text |Cite
|
Sign up to set email alerts
|

He said, she said … they said: parents' and children's assessment of children's influence on family consumption decisions

Abstract: PurposeThe purpose of this paper was to examine the impact of Israeli children on family decision making.Design/methodology/approachTwo studies were used, replicating two different approaches that have been used to measure children's influence with US children. In study one, a survey was given to each parent, whereas, in study two, a survey was given to each parent and their child.FindingsFindings indicate that Israeli children have a similar influence to US children, suggesting that, overall, Israeli children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 16 publications
2
68
0
Order By: Relevance
“…The processes of cultural change demonstrated through the types of cuisine remain relevant and are a contribution to the existing culture and authenticity literature. Future studies should include more representative samples from other ethnic and the use of multiple respondents (Shoham & Dalakas, 2005) such as look from customer perspectives and triangulation with other ethnic. It is also suggested that personal identity and social identity are two ends of a continuum with opposite effects on a same consequence (Terry & Hogg, 1996).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The processes of cultural change demonstrated through the types of cuisine remain relevant and are a contribution to the existing culture and authenticity literature. Future studies should include more representative samples from other ethnic and the use of multiple respondents (Shoham & Dalakas, 2005) such as look from customer perspectives and triangulation with other ethnic. It is also suggested that personal identity and social identity are two ends of a continuum with opposite effects on a same consequence (Terry & Hogg, 1996).…”
Section: Study Limitationsmentioning
confidence: 99%
“…As a result, the study of children's contributions to family routines is a key factor (Family Platform 2011). Noticeably, the contemporary child has a higher disposable income than children of previous generations (Lintonen et al 2007) and thus has a significant influence on family decision-making processes (Shoham and Dalakas 2005;Belch et al 2005). According to Spiro (1983), in order to understand family consumption behaviour, research should focus on the nature of children's purchase influence, moreover, studies must also examine the process flow beyond the outcomes of family decision-making.…”
Section: Youth Purchase Decisions and Their Influence On The Family Dmentioning
confidence: 99%
“…The understanding of family dynamics can provide meaningful insights into the understanding of household decision-making (Shoham and Dalakas 2005). Family communication patterns are one of the main drivers of these processes, as behavioural scientists stated, a 'culture reproduces itself through the communication activities of its members' (Viswanathan et al 2000, p. 406).…”
Section: Parent-child Communicationmentioning
confidence: 99%
“…Marketing literature (Foxman et al 1989;Belch and Willis, 2002;Shoham and Dalakas, 2005) reveal that there are many product groups of different price levels that cater to different needs and are used by different family members. It was determined that for these product groups, the stages where the adolescent influences the purchasing decision varied.…”
Section: Research Literature and Developing Hypothesesmentioning
confidence: 99%